Enhancing the Tenth-Grade Students’ Vocabulary Achievement by Using English Songs at Senior High School. - Eka Mochamad Robit Azmi (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2024)
Learning vocabulary is very important in learning a foreign language (Aminatun & Sari 2021). Vocabulary is one of the components of the English foreign language that students must master well in addition to the other components, there are some components: pronunciation, vocabulary, and grammar. Wallace (2007) pointed out that vocabulary is an important key in learning English. Rich vocabulary will help students mastering English and its four major skills which cover listening, speaking, reading, and writing (Aisyah,2017). By the explanation, mastery of vocabulary is very important in English learning. Vocabulary is the basis of all components of English learning. Mastering vocabulary is a key to improving the ability of reading, writing, speaking, and listening. The subjects of this research were the tenth-grade senior high school in Banyuwangi, the preliminary study, it was found that most students still lacked in their vocabulary mastery. English teachers always begin class by using the English language. Less than 10 kids in class of the 10th grade at this school can respond to the teacher's inquiries at the start of the lesson. Because they do not understand what the teacher is saying. A few students can directly respond to the teacher's questions if they comprehend the questions and have a sufficient vocabulary. Based on a preliminary study, it was found that the students who had scores below 75 were 16 or 56% of 30 students. Thus, this classroom action research was conducted to overcome the students' problems in vocabulary learning. The problem is the lack of vocabulary that students have, so there is a lack of understanding of the content of the teacher's communication with students during learning. One of the appropriate teaching media need to be used. Song is one of the media learning techniques that can be used to create a fun classroom atmosphere. Songs can be an effective learning tool in English classes. (Aminatun & Isnaini 2021). An English song is an interesting medium that can help the students xii memorize the words, and the lyrics song can also help the students know the meaning of the words. Four methods were used to collect the data: (1) observation, (2) vocabulary test, and (3) documentation. This study uses a cycle model with four stages of activity activities which include: (1) the planning of the action, (2) implementing the action, (3) observing and evaluation, and (4) reflection of the action (Kemmis & Taggart, 1992). This research was carried out in one cycle with three meetings conducted from August 29th to September 5th, 2024. The English teacher observed increasing the students' active participation when the researcher implemented the action. The vocabulary achievement test was given in the third meeting held on the 12th of September 2024. The results of the observation showed that there was an increase in the percentage of student activity from 67% to 83%. That means that the increase in student activity in the classroom increases when learning and teaching vocabulary activities are carried out using English songs. From the results obtained from the vocabulary achievement test, it was found that 25 students, or 83% of 30 students got a score of ≥75. That means an increase in the percentage of students who get a score of ≥75 on the vocabulary achievement test. Looking at the data analysis and discussion, it can be concluded that the use of English songs could enhance the students' active participation and the students' vocabulary achievement.
Reaploud Repository hasyim Mei 2026
Keywords: Vocabulary; Enhancing; Achievement